INOVASI PRODUK: DALAM MENINGKATKAN KINERJA USAHA MIKRO KECIL DAN MENENGAH (UMKM) - M . Trihudiyatmanto (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2022)
This research aims to analyze the effect of financial literacy, human resource competence and the position of product innovation as a mediating variable on the performance of Micro, Small and Medium Enterprises (MSMEs) in Wonosobo Regency. Hypothesis testing in this research uses Structural Equation Modeling (SEM) analysis. The population in this research is MSME actors in Wonosobo Regency with a total of 60,480 units sourced from LKPJ Wonosobo Regency in 2019. The sampling method in this research is random sampling and uses the slovin formula so that in the research 100 MSME industries are taken in Wonosobo Regency. Based on the research results, it was found that 1) there is a positive influence of financial literacy on the performance of MSMEs in Wonosobo Regency; 2) there is a positive influence of human resource competence on the performance of MSMEs in Wonosobo Regency; 3) product innovation mediates the bond between financial literacy and human resource competence. on the performance of SMEs in Wonosobo Regency.